2016
DOI: 10.1111/jns.12183
|View full text |Cite
|
Sign up to set email alerts
|

Gait in children and adolescents with Charcot‐Marie‐Tooth disease: a systematic review

Abstract: Symptoms of Charcot-Marie-Tooth (CMT) disease typically arise in childhood or adolescence with gait difficulty most common. A systematic review was conducted to synthesise, review, and characterise gait in paediatric CMT. Health-related electronic databases were reviewed with search terms related to CMT and gait. Of 454 articles, 10 articles describing seven studies met eligibility criteria; samples ranged from 1 to 81, included mixed CMT sub-types and had a participant mean age of 13 years. Assessments includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…However, we have demonstrated that its presence could modify (or at least, be related to) gait performance. Our findings are consistent with the gait alterations found in Charcot-Marie-Tooth disease[ 34 ]. With regard to the relationship between gait parameters and corpus callous thinning, we interpret it with caution.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have demonstrated that its presence could modify (or at least, be related to) gait performance. Our findings are consistent with the gait alterations found in Charcot-Marie-Tooth disease[ 34 ]. With regard to the relationship between gait parameters and corpus callous thinning, we interpret it with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Review of the literature resulted in 52 papers describing gait and functional ambulation in over eight neuromuscular diseases of childhood including CMT (15 papers), Becker and Duchenne muscular dystrophies (B/DMD) (21 papers), SMA (7 papers), congenital myotonic dystrophy (CMD) (2 papers), fascioscapulohumeral dystrophy (FSHD) (1 paper), Pompe disease (1 paper), collagen VI disorders (1 paper) and other mixed cohorts (4 papers) ( Table 1). Two papers were systematic reviews of gait in CMT [18] and DMD [28]. Several papers described the same or similar cohorts, either cross-sectional and longitudinal studies [11,16,20,21,34,35,42] or a descriptive papers of a randomised controlled trial (RCT) [24,25,38,39].…”
Section: Studies Includedmentioning
confidence: 99%
“…Therapeutic interventional studies should consider expanding on the descriptors of inclusion for pes planus in children [51][52][53] to avoid the possibility of medicalising healthy physiological development [54] and potential detriment to the health economy and the individual [55,56]. The effects of footwear as a therapeutic intervention on other noteworthy conditions that impact on children's mobility such as joint hypermobility syndrome [57], spina bifida [58], developmental coordination disorder [59], juvenile idiopathic arthritis [60], and Charcot Marie Tooth [61] were not considered in the included studies.…”
Section: Discussionmentioning
confidence: 99%